Vignettes in Patient Safety Volume 3 - Stawicki, Stanislaw P.; Firstenberg, Michael S. (IntechOpen, 2018)
Over the past decade it has been increasingly recognized that medical errors constitute an important determinant of patient safety, quality of care, and clinical outcomes. Such errors are both directly and indirectly responsible for unnecessary and potentially preventable morbidity and/or mortality across our healthcare institutions. The spectrum of contributing variables or "root causes" - ranging from minor errors that escalate, poor teamwork and/or communication, and lapses in appropriate protocols and processes (just to name a few) - is both extensive and heterogeneous. Moreover, effective solutions are few, and many have only recently been described. As our healthcare systems mature and their focus on patient safety solidifies, a growing body of research and experiences emerges to help provide an organized framework for continuous process improvement. Such a paradigm - based on best practices and evidence-based medical principles- sets the stage for hardwiring "the right things to do" into our institutional patient care matrix. Based on the tremendous interest in the first two volumes of The Vignettes in Patient Safety series, this third volume follows a similar model of case-based learning. Our goal is to share clinically relevant, practical knowledge that approximates experiences that busy practicing clinicians can relate to. Then, by using evidence-based approaches to present contemporary literature and potential contributing factors and solutions to various commonly encountered clinical patient safety scenarios, we hope to give our readers the tools to help prevent similar occurrences in the future. In outlining some of the best practices and structured experiences, and highlighting the scope of the problem, the authors and editors can hopefully lend some insights into how we can make healthcare experiences for our patients safer.